Pengukuran Komposisi Tubuh dalam Upaya Deteksi Obesitas pada Laki-laki dan Perempuan Usia Produktif di SMA Kalam Kudus II, Kelurahan Duri Kosambi, Jakarta - Alexander Halim Santoso; Fiona Valencia Setiawan; Bryan Anna Wijaya; Edwin Destra (Pusat Riset dan Inovasi Nasional, 2024)
This community service evaluated body composition in men and women of productive age at Kalam Kudus II Senior High School, Duri Kosambi, Jakarta. This community service study included 68 respondents. Measurements were carried out using a body composition scae to assess percentage of total fat, visceral fat, subcutaneous fat and total muscle. The results showed that the 51-64 year age group had the highest percentage of total and visceral fat, while the 18-35 year age group had the highest percentage of total muscle. These findings emphasize the importance of routine body composition monitoring for early detection and appropriate intervention to prevent obesity and metabolic disease. Recommended interventions include a balanced diet, increased physical activity, and health education focused on weight management and healthy body composition. The use of body composition analysis technology can provide more accurate data to support effective and measurable health programs among the productive age group.